Development of Polyurethane Elastomer-Based Bio-Composites Reinforced with Basaltic Pumice - Yurderi, Mehmet; Tayfun, Ümit; Bulut, Ahmet; Tayfun, Ümit; Yurderi, Mehmet; Bulut, Ahmet (My University, 2024)
Basaltic pumice has a black or gray appearance due to its iron and magnesium-rich komatiitic tuff composition. Pumice's porous structure allows the production of various polymer-based bio-composite materials for biomedical applications. This study developed bio-composite samples by incorporating basaltic pumice powder at 2.5, 5.0, 7.5, and 10.0 percent concentrations into an elastomeric polyurethane (EPU) matrix. The surface and elemental structure of basaltic pumice particles were investigated using the SEM/energy diffraction X-ray technique. The physical, mechanical, thermal, melt-flow, and morphological properties of bio-composites were studied experimentally. Findings showed a rise in Shore hardness and tensile modulus parameters and declined tensile elongation. According to the thermal study, introducing basaltic pumice resulted in a modest drop in the thermal stability of the EPU and an improvement in stability against mechanical deformations. Pumice loadings raised the melt flow and extrusion torque values of the EPU. The observation of the homogeneously distributed pumice particles in the EPU matrix is used as visual evidence to investigate the highest performance among the composites in the EPU sample with the lowest loading rate of 7.5% pumice. Overall, BP is effective as a reinforcing agent in EPU-based bio-composites at low additive percentages.
Keywords: Polyurethane Elastomer; Bio-composites; Basaltic Pumice; Bio-medical; Melt-blending